Anti‐VEGF‐A/ANG2 combotherapy limits pathological angiogenesis in the eye: a replication study - Anne Wolf; Thomas Langmann (EMBO Molecular Medicine)
Abstract Neovascular and inflammatory retinal diseases including wet age‐related macular degeneration (AMD) can cause severe vision loss among the elderly. Simultaneous neutralization of vascular endothelial growth factor‐A (VEGF‐A) and angiopoietin 2 (ANG2) is envisioned as a novel candidate approach to treat wet AMD with better efficacy. However, earlier published data from a genetic mouse model showed data aberrations (Regula et al, 2016). In this issue of EMBO Molecular Medicine, Foxton et al (2019) have provided compelling evidence replicating the data and confirming the overall concept that VEGF‐A/ANG2 combotherapy is effective in suppressing retinal neovascularization.